The Return on R&D Versus Capital Expenditures in the Pharmaceutical and Chemistry Industies - Hsieh,Ping-Hung; Mishra,C. S.; Gobeli,Dave (IEEE Transactions on Engineering Management, 2003)
The impact of research and development (R&D) on firm performance is generally agreed to be positive, but the nature and extent of this impact share little agreement in the previous research. Using an improved, time series, cross-sectional regression model that accounts for both contemporaneous and firm-specific serial correlation, as well as the feedback between firm profitability and investments, our study compares the rate of return from a dollar investment on R&D to a dollar investment on fixed assets in pharmaceutical and chemical industries. We find positive associations of R&D intensity and all variables of firm performance (net margin, operating margin, sales growth, and market value). We find that an investment in R&D earns an operating margin return much higher than the industry cost of capital. We also find that the effect of an investment in R&D on the firm's market value is about twice as much the effect of an investment in fixed assets. These findings have implications for corporate investment strategies, indicating that additional R&D investment is more likely to provide a firm with a unique and sustainable competitive advantage.
Keywords: Strategy & Entrepreneurship; Supply Chain

The Effectiveness of Long Term, Accounting-based Incentive Plans - Mishra,C. S.; Gobeli,Dave; May,D. (Journal of Managerial Issues, 2000)
Keywords: Strategy & Entrepreneurship

Strategic Value of Corporate Venture Capital Programs - Gobeli,Dave; Mishra,C. S. (Journal of Private Equity, 2000)
Corporate venturing activities, driven largely by the need to be competitive in the Internet Age, have out-paced the accompanying theory on how such programs can create value. This article presents a framework for understanding value creation through a firm's venture capital programs. The framework includes two stages of value creation: a firm creates value through building technology equity and brand equity, and then corporate venturing programs can multiply this value. A mediating variable, free cash flow level, is included to allow for effective use of venture funds.
Keywords: Strategy & Entrepreneurship